How do dinosaurs count to ten? - Yolen, Jane.; Teague, Mark (New York : Blue Sky Press, 2004)
Describes how a little dinosaur counts from one to ten, using the toys and other things around him.
Cover title.
On board pages.
Keywords: Dinosaurs -- Fiction; Counting; Stories in rhyme